Antileishmanial activity of the Antarctic red algae Iridaea cordata (Gigartinaceae; Rhodophyta) - Rangel, Karen C.; Debonsi, Hosana M.; Clementino, Leandro C. [UNESP]; Graminha, Marcia A. S. [UNESP]; Vilela, Leonardo Z.; Colepicolo, Pio; Gaspar, Lorena R. (Springer, 2019)
Leishmaniasis is considered a neglected disease and affects billions around the world, currently presenting few therapeutic options, which makes the development of new antileishmanial drugs urgent. Secondary metabolites from marine and terrestrial organisms are important sources of new chemical entities. Herein, the potential activity of crude extracts and fractions from the Antarctic macroalga Iridaea cordata (Turner) Bory de Saint-Vincent was studied against promastigote and intracellular amastigotes forms of Leishmania amazonensis. The cytotoxicity of the active fractions was evaluated on macrophages and 3T3 BALB/c fibroblasts. The chemical profile of volatile substances was analyzed using the GC-MS technique. The fractions IC-FE (IC50-AMA = 23.6 +/- 3.4 mu g mL(-1); SI > 11) and IC-FF (IC50-AMA = 12.4 +/- 1.2 mu g mL(-1); SI > 24) showed promising activity against amastigotes and higher selectivity to the parasite rather than to the mammalian host cells, when compared to the reference drug amphotericin B (IC50-AMA = 5.9 +/- 0.3 mu g mL(-1); SI = 3.9). Their estimated LD50 in rodents are also higher than that in amphotericin B (LD50 IC-FE = 594.5 +/- 25.87 mg kg(-1); LD50 IC-FE = 580.1 +/- 11.84 mg kg(-1); LD50 amphoter = 172.20 +/- 2.40 mg kg(-1)). The chemical profile of these fractions showed the presence of phthalates, esters, ketones, fatty acids, and carboxylic acids, which might be contributing alone or synergistically to the observed antileishmanial activity. Consequently, I. cordata might be used to identify new antileishmanial compounds.
Keywords: Cytotoxicity; Leishmanicidal; Leishmania amazonensis; GC-MS analysis; Iridaea cordata; Rhodophyta